Alterations in DNA Damage Response Pathways Underlying Acquired Resistance to Olaparib: Evidence from In Vitro Models. - Jinyan, Lan; Simin, Huang; Xiuqin, Ni; Xingxian, Luo; Hanchao, Feng (Journal of Neonatal Surgery, 2025)
DDR is a multifaceted system of cellular pathways that detect signal and repair DNA damage to preserve genome reliability. This mechanism is crucial in cancer biology, as deficiencies in DDR pathways often direct to tumor development and influence treatment responses. A PARPi, Ola, is frequently used for targeted OC, particularly in patients with BRCA2-mutated HR repair defects. OR often develops and reduces the drug's therapeutic efficacy. This research investigates the way the combination of Ola with medications targeting the ATM/WEE1 pathway increases its cytotoxicity in OROC cells with BRCA2 degeneration mutations. The antitumor effects of Ola alone and combined with these inhibitors are estimated in OC cell lines that are either sensitive (PEO1, PEO4) or resistant (PEO1-OR) to Ola. The BRCA2MUT PEO1 cells are used to create the PEO1-OR cell line. The appearance of 15 proteins linked to the DDR is adjusted using antibody microarrays. The findings showed that in both sensitive and resistant OC cells, Ola combined with ATMi or WEE1i dramatically decreased cell feasibility, and clonogenic survival, and triggered apoptosis, as evidenced by caspase-3/7 activation. The face of DDR-connected proteins concerned in DNA repair and cell cycle regulation changed significantly as a result of these combo therapies. The Ola-induced overexpression of proteins that control cell destiny following DNA damage is reversed in PEO1-OR cells when ATMi and WEE1i are present. Overall, OR to PARPi is successfully reversed by the addition of ATM or WEE1 inhibitors, which also changed the expression of important DDR-related proteins and had anti-proliferative effects on BRCA2MUT OROC cells. These results provide a potential method to circumvent OR in OC therapy by shedding light on the cellular response to a combination of Ola and ATM/WEE1 pathway inhibitors.